Nobiletin acts as a potential anticancer agent against osteosarcoma by regulating ERK and AKT signaling pathways (Bangladesh Journal of Pharmacology, 2014)
The current study was aimed to evaluate the anti-proliferative activity of nobiletin, a flavonoid, on osteosarcoma cell line, SaOS-2. Furthermore, we attempted to investigate the signaling pathways involved in the cell growth inhibition mechanism. Upon exposure, nobiletin showed significant cell inhibitory effect on SaOS-2 cells in a dose dependent manner as evidenced by MTT assay and LDH assay. Moreover, flow cytometric analysis demonstrated that upon treatment with nobiletin, SaOS-2 cells underwent apoptosis and showed increased number of cells arrested in G2/M phase. Activation of caspase-9 and -3 indicate the activation of apoptotic signaling pathway in SaOS-2 cells. Additionally, it was observed that the cell inhibitory effect was regulated by the activation of ERK signaling pathway while AKT signaling pathway was down regulated in SaOS-2 cells after 24 h of Nobiletin treatment.